Chinese investments in Africa: addressing and analysing labour, skills and technology transfer challenges - Mazire, Takudzwa (Department of Commercial Law, 2020)
This research paper provides an address and analysis of the challenges commonly faced under Chinese investments in Africa and seeks to address the question on what regulatory mechanism can be used to maximise the benefits of Chinese Investments in Africa. In doing so, this study seeks to clarify the nature activities that transpire under Chinese investment, this is because over the past decades there have been serious accusations of human rights violations, illegal practices and lack of technology and skills transfers amongst many other problems. In conducting this examination, this study, I consider the dynamic legal and policy framework that regulates the Chinese investments. This provides a vehicle through which the legality of Chinese investments actors can be tested. Secondly, an outline and discussion of two selected challenges namely, Labour relations and employment practices; lack of skill and technology transfers. These issues are analysed in depth from different perspectives and potential solutions will be provided. In addressing the challenges, I draw from the experience of South Africa in terms of employment practices and Huawei in Zimbabwe and South Africa case studies. The research ultimately concludes that the challenges faced under Chinese investments are not as described by critics but rather they are complex and differ from business to business. Therefore, the best solution may be to ensure effective enforcement and implementation of local laws to ensure compliance with the law. The study recommends that there is a need for Africa to have a uniform China policy and to take advantage of the FOCAC process to prioritise the areas critical to their national and continental development goals.